Modeling the Dynamics of Processes in the Labor Market at the State Level, Applying a Model of Competition with Self-Regulation of Numbers - Saidkarimovich Ziyadullaev, Nabi; Vasilyevich Lyasnikov, Nikolay; Danilovich Katulsky, Evgeniy; Vladimirovna Vysotskaya, Nataliya; Anatolievna Pak, Olga; ., . (International Journal of Engineering and Technology, 2018)
The article reviews possibilities of economic and mathematical modeling in labor market management. A model of the dynamics of processes in the labor market at the state level, applying a model of competition with self-regulation of numbers, is presented. Â